Monitoring Korosi Discharge Conveyor E pada Tambang Batubara PT XYZ di Kabupaten Sarolangun, Provinsi Jambi - Aristu Eka Adrian; Elfida Moralista; Zaenal (Bandung Conference Series: Mining Engineering, 2023)
Abstract. Conveyors structure made from carbon steel are susceptible to corrosion which will reduce the quality of the material. The corrosion that occurs will affect the Remaining Service Life on the conveyor structure. Therefore, the purpose of this research is to determine the type of corrosion, corrosion control that is applied to the conveyor structure, the value of Corrosion Rate and Remaining Service Life.The measurement methodology for the 142 meter long conveyor structure consisting of 4 segments with 32 test points was carried out based on the thickness reduction method. Measurement of the actual thickness of the conveyor structure was carried out using an Ultrasonic Thickness Gauge TT 130. In this study, observations of environmental conditions in 2016-2020 showed that the average air temperature data was 25.34oC, average rainfall was 209.97 mm/year and 86.92% relative humidity. The type of corrosion that occurs on the conveyor structure is uniform corrosion. The corrosion control method applied to the conveyor structure is the coating method with a three-layer system using Seaguard 5000 primer coating, Sherglass FF intermediate coating, and Aliphatic acrylic modified polyurethane top coating. Based on data on reducing the thickness of the conveyor structure with values ranging from 1.31-2.35 mm, a Corrosion Rate is obtained with a value of 0.1871-0.3357 mm/year, based on the table of relative corrosion resistance of steel this value is included in the good category. The service life of the conveyor structure is 7 years with a Remaining Service Life value ranging from 6.58-9.01 years. Therefore there are 14 or 43.75% of the 32 test points which are predicted not to reach the design life of 15 years. Abstrak. Struktur Conveyor berbahan dasar baja karbon rentan mengalami terjadinya korosi yang akan mengurangi kualitas material.. Korosi yang terjadi akan berpengaruh terhadap Remaining Service Life pada struktur conveyor. Maka dari itu tujuan dilakukannya penelitian ini untuk mengetahui jenis korosi, pengendalian korosi yang diaplikasikan pada struktur conveyor, nilai Corrosion Rate dan Remaining Service Life. Metodologi pengukuran pada struktur conveyor sepanjang 142 meter yang terdiri dari 4 segmen dengan 32 test point dilakukan berdasarkan metode pengurangan ketebalan. Pengukuran tebal aktual struktur conveyor dilakukan dengan menggunakan alat Ultrasonic Thickness Gauge TT 130. Pada penelitian ini, pengamatan kondisi lingkungan pada tahun 2016-2020 menunjukan bahwa data temperatur udara rata-rata 25,34oC, curah hujan rata-rata 209,97 mm/tahun dan kelembapan relatif 86,92%. Jenis korosi yang terjadi pada struktur conveyor yaitu korosi merata. Metode pengendalian korosi yang diaplikasikan pada struktur conveyor yaitu metode coating dengan sistem three layer system menggunakan primer coating Seaguard 5000, intermediate coating Sherglass FF, dan top coating Aliphatic acrylic modified polyurethane. Berdasarkan data pengurangan ketebalan struktur conveyor dengan nilai berkisar antara 1,31-2,35 mm, didapatkan Corrosion Rate dengan nilai 0,1871-0,3357 mm/tahun, berdasarkan tabel ketahanan korosi relatif baja nilai tersebut termasuk ke dalam kategori good. Umur pakai struktur conveyor 7 tahun dengan nilai Remaining Service Life berkisar antara 6,58-9,01 tahun. Oleh karena itu terdapat 14 atau 43,75% dari 32 test point diprediksi tidak dapat mencapai umur desainnya yaitu 15 tahun.